2016
DOI: 10.1007/s00216-016-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of colon cancer metastasis: comparative mass spectrometric analysis of the isogenic primary and metastatic cell lines SW480 and SW620

Abstract: The contributions of phosphorylation-mediated signaling networks to colon cancer metastasis are poorly defined. To interrogate constitutive signaling alterations in cancer progression, the global phosphoproteomes of the patient-matched SW480 (primary colon tumor origin) and SW620 (lymph node metastasis) cell lines were compared with TiO2 and IMAC phosphopeptide enrichment followed by LC-MS/MS. Network analysis of the significantly altered phosphosites revealed differential regulation in cellular adhesion, mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…New insights into the molecular mechanisms of CRC metastasis will undoubtedly be beneficial for developing more effective drugs. [3][4][5] Extensive studies have been completed with the goal of understanding CRC metastasis at the transcriptome level, generating tremendous information about the landscape of mRNA across different stages of CRC. [6,7] However, nucleic-acid-based measurements do not correlate with protein abundance, which are the primary effectors of function in biology.…”
Section: Deep Tdp Of Human Colorectal Cancer Cell Lines-pagementioning
confidence: 99%
See 1 more Smart Citation
“…New insights into the molecular mechanisms of CRC metastasis will undoubtedly be beneficial for developing more effective drugs. [3][4][5] Extensive studies have been completed with the goal of understanding CRC metastasis at the transcriptome level, generating tremendous information about the landscape of mRNA across different stages of CRC. [6,7] However, nucleic-acid-based measurements do not correlate with protein abundance, which are the primary effectors of function in biology.…”
Section: Deep Tdp Of Human Colorectal Cancer Cell Lines-pagementioning
confidence: 99%
“…[8] Quantitative bottom-up proteomics (BUP) studies of metastatic and nonmetastatic CRC cell lines have been completed to discover new protein regulators involved in CRC metastasis. [4,9,10] Unfortunately, those BUP studies provided limited information of the proteoforms. These proteoforms represent all possible protein molecules derived from the same gene resulting from genetic variations, RNA alternative splicing, and protein post-translational modifications (PTMs).…”
Section: Deep Tdp Of Human Colorectal Cancer Cell Lines-pagementioning
confidence: 99%
“… Ludvigsen et al (2020) compared a normal derived colon mucosa cell line (NCM460) and a colon cancer cell line (HCT116) to identify protein biomarkers with increased expression in colorectal cancer, including retinol-binding protein 1. 2D cell culture has also been used to compare non-metastatic (SW480) and metastatic colon cancer cell lines (SW620) ( Zhao et al, 2007 ; Schunter et al, 2017 ; Torres et al, 2018 ). These two cell lines derive from the same patient (Stage II for SW480 and Stage III for SW620).…”
Section: D Cell Culturementioning
confidence: 99%
“…Moreover, the greatest increase in phosphorylation of Ser2 of eIF2S2 without any changes in eukaryotic initiation factor 4E (eIF4E) expression was observed in the SW620 cell line. Altogether, they suggested that metastatic cells deregulate mRNA stability and translational efficiency with constitutive changes to the phosphoproteome [ 89 ]. In another study, the phosphorylation ratio of serine, threonine and tyrosine amino acids was identified as 90%, 10% and <1% respectively (8).…”
Section: Phosphoproteomics In Gi Cancersmentioning
confidence: 99%